THE MODELING OF THE EXPLOITATION PROCESS OF GAS DEPOSIT ACCORDING TO INHOMOGENEOUS STRATUM STRUCTURE - Artem Viktorovich Plotnikov (Современная наука и инновации, 2022)
The article is provided the process of mathematical modeling process of gas deposit according to its inhomo_geneous structure. The discrete analogue of the mathematical model was created to perform a computational experiment. The results of the experiment reflecting change of stratum pressure and production rates are presented in graphical form.